2021
DOI: 10.3390/vaccines9070709
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Coverage and Intention to Receive Hypothetical Ebola and COVID-19 Vaccines among Medical Students

Abstract: The study aimed to determine influenza vaccine uptake among medical students and their intention to receive a hypothetical Ebola or COVID-19 vaccine. This cross-sectional questionnaire-based study was performed in 2015 and 2020 on 675 medical students at the Medical University of Warsaw, Poland. In 2020, the influenza vaccination coverage was 36.5%, and students were almost five times more likely to be vaccinated than in 2015 (OR = 4.8; 95% CI: 3.1–7.5). In 2020, the survey was conducted during the first unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The estimated total COVID-19 vaccination acceptance rate among HCSs was 68.8% (95% CI: 60.8–76.3% I 2 = 100%) ( Figure 2 ). Talarek et al [ 56 ] observed the highest acceptance rate (95.6%, 95% CI: 92.0–96.6%) in a study in Poland. The study in Kazakhstan by Bolatov et al [ 40 ] reported the lowest vaccination acceptance rate of 22.4% (95% CI: 19.7–25.3%).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated total COVID-19 vaccination acceptance rate among HCSs was 68.8% (95% CI: 60.8–76.3% I 2 = 100%) ( Figure 2 ). Talarek et al [ 56 ] observed the highest acceptance rate (95.6%, 95% CI: 92.0–96.6%) in a study in Poland. The study in Kazakhstan by Bolatov et al [ 40 ] reported the lowest vaccination acceptance rate of 22.4% (95% CI: 19.7–25.3%).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to vaccine acceptance rates for health science students worldwide, the vaccine acceptance rate in Morocco (26.9%) ranks the lowest among all other countries reported. Moreover, previous studies suggest significant variation in vaccine acceptance rates between and within countries, 34.9% in Egypt [22], 35% in three European countries [23], 37.3% in Uganda [24], 56% in USA [25], 58.8% in China [26], 77% in USA [27], 84.3% in China [28], 89.4% in India [29], and 94.6% in Poland [30]. However, between country income groups, a study of 6639 dental students from 22 countries found participants from low-and middle-income countries had significantly lower rates of COVID-19 vaccine acceptance compared to peers from high-income countries [31].…”
Section: Discussionmentioning
confidence: 96%
“…If we compare the coverage achieved with that obtained in another study conducted in Spain in 2017 with nursing students, we see that it is considerably higher, since the coverage achieved in that study was 15.2% [19]. Internationally, there are studies that have identified higher coverages, such as the one conducted in Poland among medical students where influenza coverages reached up to 44.4% [20]; there was another one conducted in the United Kingdom among nursing students where coverage in 2019 reached up to 47.8% [21], one in California among public health students where coverage was 43.0% (2018) [22] and 52.4% in another study conducted among nursing students in Canada in 2019 [23]. However some studies present similar coverages of 38.4% [24], 36.7% [21] and 27.3% [25], or lower ones of 27.3% [26] and 16.5% [27].…”
Section: Influenza Vaccination Coveragementioning
confidence: 87%